Public Health Surveillance for Adverse Events Following Covid-19 Vaccination in Africa: Rare Adverse Events and Fatal Cases Following COVID-19 Vaccination in Africa - Anjorin, AbdulAzeez; Odetokun, Ismail; Nyandwi, Jean; Elnadi, Hager; Awiagah, Kwame; Eyedo, Joseph; Abioye, Ajibola; Gachara, George; Maisara, Aala; Razouqi, Youssef; Mohamed, Yusuf, Mohamud; Mhgoob, Zuhal; et al. (My University, 2022)
Background: The death toll and economic disaster caused by SARS-CoV-2/ COVID-19 is still on the rise globally and in Africa with a case fatality ratio (CFR), 2.58 from 220,958 deaths out of 8,556,890 cases recorded across the continent as of 14th November 2021. Local, national and international health agencies have advocated multi-pronged public health strategies to limit infections and prevent deaths. The availability of a safe and effective vaccine is critical in the control of a pandemic. Several adverse events have been reported globally for different vaccines including COVID-19 with limited or no data from Africa. Methods: This cross-sectional epidemiological study investigated the adverse events following COVID-19 vaccination in Africans between April- June, 2021 using a structured questionnaire distributed via the web for public health surveillance. Results: Out of the 1200 participants recruited, a total of 80.8% (n = 969) respondents from 35 countries including 22 African countries and 13 countries where Africans live in the diaspora reported different adverse events following COVID-19 vaccination. More than half of the vaccinee were male (53.0%) and frontline healthcare workers (55.7%), respectively. A total of 15.6% (n = 151) reported previous exposure to SARS-CoV-2 while about one-fourth, 24.8% (n = 240) reported different underlying health conditions prior to vaccination. Fatal cases were 5.1% (n = 49) while other significant heterogenous events were reported in three categories: very common, common, and uncommon adverse events including enlarged lymph nodes 2.4% (n = 23), menstrual disorder 0.5% (n = 5), and increased libido 0.2% (n = 2). Conclusions: The study provided useful data for concerned authorities and institutions to prepare plans that will address issues related to COVID-19 vaccines.
Keywords: Vaccine adverse events; SARS-CoV-2; COVID-19 vaccine; Public health; Vaccination; Adverse events following immunization (AEFI)